Comparison of the performance of ballistic schottky barrier graphene nanoribbon FET - Ahmed, Sheikh Ziauddin; Shawkat, Mashiyat Sumaiya; Chowdhury, Md. Iramul Hoque (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.